(untitled) (Journal of Pharmaceutical Negative Results, 2022)
We are impacted by Internet connectivity and connect to the outside world using the global positioning system (GPS). We can use GPS to locate a person in a fully connected area which makes it possible to identify his location but in cases where the Global Positioning System (GPS) is not available there is no alternative to communicate to the other user specially when they are in critical situations. The work shows an effective local positioning technique using the trilaterationalgorithm which not only identifies the location of the user but also tries to analyze the locateddata through different evaluated mechanism such as packet delivery ratio, Inter arrival time and packet loss. The entire local positioning system uses the anchor nodes and Receiver Signal Strength Indicator (RSSI) values of its own Wi-Fi network to locate the user in unfavorable situations where he/she may not have chosen to be. Simulations in mat lab tool were taken for single cases of single channel node position and multiple node position. However, when we test for multiple node positions, the error or delay is greater in comparison. The hardware demonstration shows the positioning scenarios by taking anchor positioning of the nearby network in terms of coordinates i.e. ‘x’,’y’, ‘z’ and measures the signal strength of its locations and pageant the distance from the measured coordinates.